SINTAGMA DAN SISTEM PADA RITUAL POSUO PEREMPUAN BUTON - Jefrianto Syahrir; Tadjuddin Maknun; Munira Hasjim (fakultas Ushuluddin dan Dakwah IAIN Bone, 2021)
Studyng the posuo traditional rituals carried out by the people of Buton we will talk about what is contained in the ritual. Posuo for the Buton community is a transitional ritual or ceremony for Buton women who have entered puberty, a transition from adolescence to adulthood. For the people of Buton, this ritual is not merely a routine of adat, but substantially has its own meaning through a system integrated in it. Through semiotic analysis with the theory used by Ferdinand de Saussure, it can be studied that the posuo traditional ritual applied to Buton women is a contextual language system that clearly contains certain meanings. The elements that build this posuo ritual so that it becomes meaningful is certainly related to the sign system as a symbol. As a language system, posuo rituals for Buton women will be described through sintagma and system studies. Keywords :Posuo Costum Ritual, Buton, Saussure Semotics